PENGARUH PEMBELAJARAN ONLINE DI TENGAH PANDEMI COVID-19 TERHADAP HASIL BELAJAR TEMA 9 KELAS V SD NEGERI CEMPAKA 01 TEGAL - Muttaqin, Muh; Listyarini, Ikha; Agustini, Ferina (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
This study was conducted to determine the effect of online learning in the Covid-19 pandemic on learning outcomes in the 9th-grade theme of SDN Cempaka 01 Tegal. Type of quantitative research. The population in the study were all fifth-grade students of SD N Cempaka 01 Tegal. The research method used is a survey method. Singarimbun (2011: 3) explains that research with this survey method is a study that takes a sample from a population and uses a questionnaire as the main data collection tool. The questionnaire is a data collection tool that is done by giving a set of questions or written statements to the respondent to answer. The results showed that there was a positive influence on student learning outcomes. This is evidenced by the results of the analysis showed that the calculation of the product-moment correlation (rxy) between online learning (X) and learning outcomes (Y) obtained a correlation coefficient of 0.570. The coefficient r table with a significance level of 5% and N = 18 is 0.468. These results indicate that rcount is greater than rtable so that Ho is accepted. It can be concluded that there is a positive and significant influence between online learning in the Covid 19 Pandemic and the learning outcomes of Class V students at SDN Cempaka 01 Tegal.